A Reappraisal of the Migration-Development Nexus : Testing the Robustness of the Migration Transition Hypothesis - Berthiaume, Nicolas; Leefmans, Naomi; Oomes, Nienke; Rojas-Romagosa, Hugo; Vervliet, Tobias (World Bank, Washington, DC, 2021)
This paper tests the migration transition hypothesis that emigration flows first increase and later decrease with a country’s economic development. Using a migration version of the gravity model, this hypothesis is tested on a global panel data set comprising 180 origin and destination countries and a 50-year timeframe (1970-2020). This is the most extensive panel data set used so far to test the migration transition hypothesis. The results confirm the existence of an inverted U-shaped relationship between development and emigration within a cross-country panel setting. Nevertheless, the migration hump cannot be interpreted as a causal relationship: for a given low-income country, an increase in economic development is not found to lead to higher emigration. For a subsample of 44 countries that have transitioned from low-income to middle-income status, emigration has rather declined with economic development. The migration transition hypothesis is therefore unfounded. Instead, the migration hump appears to be driven by an underlying cross-sectional pattern that cannot be fully controlled: middle-income countries tend to exhibit higher emigration rates than low- or high-income countries. The findings of this paper have important policy implications: development programs can simultaneously promote economic development and reduce emigration.